Wide-field fluorescent nanodiamond spin measurements toward real-time large-area intracellular thermometry - Yushi Nishimura (Nature Portfolio, 2021)
Abstract Measuring optically detected magnetic resonance (ODMR) of diamond nitrogen vacancy centers significantly depends on the photon detectors used. We study camera-based wide-field ODMR measurements to examine the performance in thermometry by comparing the results to those of the confocal-based ODMR detection. We show that the temperature sensitivity of the camera-based measurements can be as high as that of the confocal detection and that possible artifacts of the ODMR shift are produced owing to the complexity of the camera-based measurements. Although measurements from wide-field ODMR of nanodiamonds in living cells can provide temperature precisions consistent with those of confocal detection, the technique requires the integration of rapid ODMR measurement protocols for better precisions. Our results can aid the development of camera-based real-time large-area spin-based thermometry of living cells.